Membrane Proteins Production for Structural Analysis - Mus-Veteau, Isabelle; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2014)
This volume reviews the latest development in production, stabilization and structural analysis techniques of membrane proteins. It contains 14 chapters exploring topics including the advances in heterologous expression systems, stabilization tools and structural methods that contributed to the growing number of recombinant integral membrane protein structures solved in the past few years. Each chapter was written by internationally renowned scientists in the field of membrane proteins structural characterization. Membrane proteins account for roughly 30 percent of all open reading frames in fully sequenced genomes. However, to date, atomic structures have so far been obtained for only 424 integral membrane proteins, with 100 new structures determined in the last two years. Only 10 percent of the unique integral membrane protein structures are derived from vertebrates. In general, integral membrane proteins are present in tissues at very low concentration, making production of recombinant proteins in heterologous systems suitable for large scale production a prerequisite for structural studies. Since the first atomic structures of recombinant mammalian integral membrane proteins published in 2005 (the calcium ATPase SERCA 1A and a voltage-dependent potatium channel), the structures of 37 recombinant mammalian integral membrane proteins, from which 20 belong to the G Protein Coupled Receptors family, have been solved.
1 Membrane Proteins Production for Structural Analysis -- 2 Membrane Protein Quality Control in Cell-Free Expression Systems: Tools, Strategies and Case Studies -- 3 Bacterial Expression and Stabilization of GPCRs -- 4 Membrane Protein Production in Escherichia Coli: Overview and Protocols -- 5 Lactococcus Lactis, Recent Developments in Functional Expression of Membrane Proteins -- 6 Over expression of Membrane Proteins in Saccharomyces Cerevisiae for Structural and Functional Studies: a Focus on the Rabbit Ca2+-ATPase Serca1a and on the Yeast Lipid “Flippase” Complex Drs2p/Cdc50p -- 7 Amphipols: a General Introduction and Some Protocols -- 8 New Amphiphiles to Handle Membrane Proteins: “Ménage à Trois” between Chemistry, Physical-Chemistry and Biochemistry -- 9 Building Model Membranes with Lipids and Proteins: Dangers and Challenges -- 10 Analytical Ultracentrifugation and Size Exclusion Chromatography Coupled to Light Scattering for the Characterization of Membrane Proteins in Solution -- 11 Lipidic Cubic Phase Technologies for Structural Studies of Membrane Proteins -- 12 Micelles, Bicelles, Amphipols, Nano discs, Liposomes or Intact Cells: the Hitchhiker's Guide to the Membrane Protein Study by NMR -- 13 Foundations of Bio molecular Simulations: A Critical Introduction to Homology Modeling, Molecular Dynamics Simulations and Free Energy Calculations of Membrane Proteins -- 14 Structural Studies of TSPO, a Mitochondrial Membrane Protein.
Keywords: Cell biology; Cell membranes .; Proteins .; Cell Biology; Membrane Biology; Protein Science